A new structurally preserved fossil umbrella pine from the Jurassic of East Asia. Issue 9 (15th June 2022) - Jiang, Zikun; Tian, Ning; Wang, Yongdong; Li, Ya; Zheng, Shaolin; Xie, Aowei; Zhu, Yanbin
Abstract : The Sciadopityaceae are today a monotypic and relict family of the Coniferales, restricted to Japan with an endemic species of Sciadopitys verticillata Sieb. et Zucc., known as umbrella pine. Megafossil remains assigned to the Sciadopityaceae have been reported from various parts of the boreal hemisphere. However, structurally preserved fossil wood of the Sciadopityaceae is poorly documented. Here we present an anatomically preserved fossil wood of the Sciadopityaceae from the Jurassic of East Asia. A new fossil wood Zhangoxylon yanliaoense gen. et sp. nov. is proposed for the specimens, which are anatomically characterized by a heterogeneous pith, endarch primary xylem, and special secondary xylem. The anatomical structures of the new genus are similar to those of the living Sciadopitys except for the type of radial pitting. The present specimen has an araucarian radial pitting, while that of the living Sciadopitys is abietinean. Therefore, Zhangoxylon gen. nov. from the Middle to Late Jurassic (Callovian to Kimmeridgian) in western Liaoning may represent the Sciadopitys ‐like petrified wood which bears pith and primary xylem. This new fossil, so far, the best‐known fossil wood of the family Sciadopityaceae, sheds light on the early evolutionary history of the family Sciadopityaceae, and contributes to a better understanding of the palaeoenvironment of the Jurassic Yanliao Biota in East Asia. Abstract : The Sciadopityaceae are today a monotypic and relict family of the Coniferales, restricted to Japan with an endemic species of Sciadopitys verticillata Sieb. et Zucc., known as umbrella pine. Megafossil remains assigned to the Sciadopityaceae have been reported from various parts of the boreal hemisphere. However, structurally preserved fossil wood of the Sciadopityaceae is poorly documented. Here we present an anatomically preserved fossil wood of the Sciadopityaceae from the Jurassic of East Asia. A new fossil wood Zhangoxylon yanliaoense gen. et sp. nov. is proposed for the specimens, which are anatomically characterized by a heterogeneous pith, endarch primary xylem and special secondary xylem. The anatomical structures of the new genus are similar to those of the living Sciadopitys except for the type of radial pitting. The present specimen has an araucarian radial pitting, while that of the living Sciadopitys is abietinean. Therefore, Zhangoxylon gen. nov. from the Middle to Late Jurassic (Callovian to Kimmeridgian) in western Liaoning may represent the Sciadopitys ‐like petrified wood which bears pith and primary xylem. This new fossil, so far, the best‐known fossil wood of the family Sciadopityaceae, sheds light on the early evolutionary history of the family Sciadopityaceae, and contributes to a better understanding of the palaeoenvironment of the Jurassic Yanliao Biota in East Asia.